Getting back to the event: COVID-19, attendance and perceived importance of protective measures - Peric, M.; Wise, N.; Heydari, R.; Keshtidar, M.; Mekinc, J. (Kinesiology, 2021)
Current COVID-19 realities have led to event disruptions, and new policies on who can be in event venues mean event organisers must consider and implement new protective measures for the safety and security of both active and passive participants. This empirical study focuses on event consumers and issues related to their intention to attend future sporting events and their perception of how important they find some of the safety-related protective measures when attending sporting events as spectators or competitors following the COVID-19 crisis. The results suggest that, once all restrictions on movement and sporting event attendance have been revoked, most of the respondents from one Middle East and two European countries will attend events in their home country within few weeks. In addition, the respondents from the country that experienced more severe consequences of the pandemic perceive all protective measures as more important than the respondents from countries that were less affected.